Xavier Mina en la historiografía española y americana - Ortuño Martínez, Manuel (Huarte de San Juan. Geografía e Historia, 1998)
Xavier Mina, a mexican hero, has been unknown by the spanish historians, who generally confounded him with his uncle Espoz y Mina, the great defender of the Constitutional Triennium against the followers of the tyrannical Ferdinand VII. Here is an analysis of the mistakes that there is still about both of them as appears in the large amount of the consulted works and authors. Also a complete selection of articles and books published in Spain and abroad and a full list of references about the young spanish liberal, published or not, begining with the Journal of the Expedition, signed by James A. Brush in 1818. Xavier Mina, who died in 1817, is one lost link between the first liberals, who were fighting in America against Ferdinand VII, followers of the radical wing of Florez Estrada, and the ’Revolucion de Riegel’ held in 1820.